Pengaruh Metode Drill terhadap Kemampuan Penggunaan Tanda Baca pada Pembelajaran Bahasa Indonesia Siswa Kelas V Sekolah Dasar Swasta Alwashliyah Indrapura - Siti Nur’ibni Aulia Hutagalung; Rizky Seni Utami; Sutarini Sutarini (ARZUSIN, 2026)
Students’ difficulties in understanding the use of punctuation in Indonesian language learning remain an obstacle that hinders the development of their effective writing skills. This study aimed to determine the effect of the drill method on the ability to use punctuation in Indonesian language learning among Grade V students at Alwashliyah Indrapura Private Elementary School. The research instrument consisted of 33 multiple-choice items, which were validated through a trial with 25 students from another school, resulting in 25 valid items with a reliability coefficient of 0.733, indicating a reliable category. The study employed a pretest–posttest design involving 25 students as the sample. Baseline data were obtained through a pretest, after which the drill method was implemented over several sessions to repeatedly practice the use of various punctuation marks. The results showed a significant improvement in students’ punctuation abilities, with the mean pretest score of 57.68 increasing to 75.76 in the posttest. The Shapiro–Wilk normality test indicated that the data were normally distributed, while the paired sample t-test yielded a significance value of < 0.001, indicating that the drill method had a significant effect on improving students’ abilities. Indicator-level analysis demonstrated improvement across all types of punctuation tested, thereby confirming that the drill method is effective in enhancing the accuracy and skill in punctuation use. These findings affirm that the drill method can serve as an alternative instructional strategy in Indonesian language learning at the elementary school level to optimize students’ mastery of punctuation.